Integrative taxonomy reveals mitochondrial introgression and Pleistocene diversification in Palearctic Agnocoris species (Insecta: Heteroptera: Miridae) - Dzhelali, Polina A.; Namyatova, Anna A. (Zootaxa, 2025)
The genus Agnocoris (Heteroptera: Miridae: Mirinae: Mirini) includes seven species and three of them, A. rubicundus, A. reclairei, and A. eduardi, are distributed in the Palearctic. This study represents the first integrative taxonomic assessment of Palearctic Agnocoris, combining morphological and molecular data (COI, 16S rRNA, ITS1, Ca-ATPase) to clarify species boundaries, phylogenetic relationships, and biogeographic history. This study showed that the three Palearctic species are very similar to each other externally, and male and female genitalia structures should be used for the correct species identification. A revised diagnosis and identification key for Palearctic Agnocoris representatives, as well as novel characters that can be used for the generic diagnosis, are provided. Phylogenetic analyses revealed discordance between mitochondrial and nuclear markers: mitochondrial data did not support the monophyly of A. rubicundus and A. reclairei, while nuclear markers confirmed their distinctiveness, suggesting historical mitochondrial introgression likely due to hybridization. The results showed that ITS1 was the most effective for the species identification and delimitation. Species delimitation methods based on this marker validated both species as separate. Divergence dating analysis suggests that Nearctic and Palearctic lineages of Agnocoris separated in Miocene. Our analysis demonstrated that A. rubicundus and A. reclairei most probably diverged ca. 1 Mya during the Pleistocene. Our findings emphasize the importance of integrative approach combining thorough morphological examinations and multiple genetic markers for accurate species delimitation in Miridae.